1997
DOI: 10.1097/00003246-199708000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Practice guideline for arterial blood gas measurement in the intensive care unit decreases numbers and increases appropriateness of tests

Abstract: Implementation of this guideline for arterial blood gas measurement increases efficiency of test utilization without prolonging mechanical ventilation or affecting outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 11 publications
2
52
0
Order By: Relevance
“…Great personnel and financial resources are required to develop guidelines. Disappointingly, observational studies [1][2][3][4][5][6][7] and randomized controlled trials 8 conducted within the intensive care unit (ICU) have generally shown no clear benefit from the use of guidelines as measured by improvements in processes and outcomes of patient care. High quality professional society practice guidelines such as the recent guidelines for the prevention of ventilator associated pneumonia jointly developed by the Canadian Critical Care Society (CCCS) and the Canadian Critical Care Trials Group 9 may have had a different effect, but this has not been measured.…”
Section: Conclusion : De Nombreuses Institutions Canadiennes Dévelop-mentioning
confidence: 99%
“…Great personnel and financial resources are required to develop guidelines. Disappointingly, observational studies [1][2][3][4][5][6][7] and randomized controlled trials 8 conducted within the intensive care unit (ICU) have generally shown no clear benefit from the use of guidelines as measured by improvements in processes and outcomes of patient care. High quality professional society practice guidelines such as the recent guidelines for the prevention of ventilator associated pneumonia jointly developed by the Canadian Critical Care Society (CCCS) and the Canadian Critical Care Trials Group 9 may have had a different effect, but this has not been measured.…”
Section: Conclusion : De Nombreuses Institutions Canadiennes Dévelop-mentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18] Using protocols for sampling ABGs has shown enhanced rates of correct indwelling arterial line placement and appropriate ABG sampling. 9,10 Specifically, Browning et al 10 evaluated respiratory therapists' effectiveness in determining when to sample ABGs.…”
Section: Are Respiratory Protocols Effectivementioning
confidence: 99%
“…Subsequent studies have confirmed the value of protocols in improving the allocation of ABGs in the ICU, and in directing the placement of indwelling arterial catheters. Pilon et al 12 conducted an observational cohort study with a before-and-after design, in which the rate of appropriately drawn ABGs increased from 44% at baseline to 78% and 79% at 2 and 13 months after protocol implementation, respectively. Associated benefits with implementing the aforementioned protocol included a reduced mean number of ABGs drawn per patient per day (from 4.9 to 2.4 -3.1, P Ͻ .001), and a concomitant cost savings of $19.18 Canadian per patient per day.…”
Section: Are Respiratory Protocols Effectivementioning
confidence: 99%
“…Impact is generally evaluated by investigating multiple clinical and cost outcomes before and after guideline implementation or by comparing the outcomes of 2 groups of patients who have been randomized to guideline-based interventions or usual care. Two randomized control trials, 42,43 3 quasiexperimental designs, 3,44,45 and 3 observational studies 21,46,47 were identified that investigated the impact of practice guidelines on clinical and cost outcomes. These studies generally measured clinician adherence with practice guidelines and compared patient outcomes in the experimental verses control groups.…”
Section: Impact On Patient Outcomesmentioning
confidence: 99%
“…The majority was found in specialized medical journals, but several included nurses as first authors 18,19 or members of the research team and coauthors. 20,21 The authors were largely health services researchers and clinicians affiliated with major medical and research institutions. Much of the work was funded by public or private health services research grants.…”
mentioning
confidence: 99%